Cerebrospinal fluid neurofilament light chain differentiates primary psychiatric disorders from rapidly progressive, Alzheimer's disease and frontotemporal disorders in clinical settings. Issue 11 (1st February 2022) - Eratne, Dhamidhu; Loi, Samantha M.; Li, Qiao‐Xin; Stehmann, Christiane; Malpas, Charles B.; Santillo, Alexander; Janelidze, Shorena; Cadwallader, Claire; Walia, Nirbaanjot; Ney, Blair; Lewis, Victoria; Senesi, Matteo; et al.
Abstract: Introduction: Many patients with cognitive and neuropsychiatric symptoms face diagnostic delay and misdiagnosis. We investigated whether cerebrospinal fluid (CSF) neurofilament light (NfL) and total‐tau (t‐tau) could assist in the clinical scenario of differentiating neurodegenerative (ND) from psychiatric disorders (PSY), and rapidly progressive disorders. Methods: Biomarkers were examined in patients from specialist services (ND and PSY) and a national Creutzfeldt‐Jakob registry (Creutzfeldt‐Jakob disease [CJD] and rapidly progressive dementias/atypically rapid variants of common ND, RapidND). Results: A total of 498 participants were included: 197 ND, 67 PSY, 161 CJD, 48 RapidND, and 20 controls. NfL was elevated in ND compared to PSY and controls, with highest levels in CJD and RapidND. NfL distinguished ND from PSY with 95%/78% positive/negative predictive value, 92%/87% sensitivity/specificity, 91% accuracy. NfL outperformed t‐tau in most real‐life clinical diagnostic dilemma scenarios, except distinguishing CJD from RapidND. Discussion: We demonstrated strong generalizable evidence for the diagnostic utility of CSF NfL in differentiating ND from psychiatric disorders, with high accuracy.